The study of pinch regimes based on radiation-enhanced compression and anomalous resistivity phenomena and their effects on hard x-ray emission in a Mather type dense plasma focus device (SABALAN2) - Piriaei, D.; Mahabadi, T. D.; Javadi, S.; Ghoranneviss, M.; Saw, S. H.; Lee, S. (AIP Publishing, 2015)
In this study, by using argon and nitrogen as the filling gases in a Mather type dense plasma focus device at different values of pressure and charging voltage, two different kinds of pinch regimes were observed for each of the gases. The physics of the pinch regimes could be explained by using the two versions of the Lee’s computational model which predicted each of the scenarios and clarified their differences between the two gases according to the radiation-enhanced compression and, additionally, predicted the pinch regimes through the anomalous resistivity effect during the pinch time. This was accomplished through the fitting process (simulation) on the current signal. Moreover, the characteristic amplitude and time scales of the anomalous resistances were obtained. The correlations between the features of the plasma current dip and the emitted hard x-ray pulses were observed. The starting time, intensity, duration, and the multiple or single feature of the emitted hard x-ray strongly correlated to the same respective features of the current dip.